Awareness and Acceptability of The University's Vision, Mission, Goals, and Objectives in Bachelor of Science in Electrical Engineering Program - Exur B. Dela Cruz; Jasky Razon; Joshua D. Dayao; Kieth Rean C Garcia; Mark Angel M. Manuel; Genesis C. Tiria; Alma L. Tangcuangco (Universitas Pendidikan Indonesia (UPI), 2022)
This study focused on determining the awareness and acceptance of the University in the Electrical Engineering Program. The research employed a descriptive research design for the survey method. The survey respondents were the University's internal stakeholders consisting of faculty members and students and external stakeholders. Weighted Mean and Analysis of Variance were utilized to determine any significant differences in the stakeholders' responses. Results showed that the stakeholders, in general, are moderately aware of the University's vision, mission, goals, and objectives. The faculty and alumni were highly aware of the Vision, Mission, Goals, and Objectives (VMGOs), while the parents were least aware. In terms of acceptance of the stakeholders in the VMGO, all stakeholders had very high acceptance of the University's vision, mission, goals, and objectives. In establishing the awareness and acceptability of the VMGO, most stakeholders have agreed on the proposed actions. Based on the findings, it can be concluded that the VMGO of the University is well formulated but not fully understood and not well disseminated based on the high level of acceptance but a moderate level of awareness among stakeholders. Thus, it is recommended that the University constantly works for a more comprehensive effort in disseminating the VMGO through the use of many forms of communication medium.